The War of the Roses [videorecording (DVD)] - DeVito, Danny; DeVito, Danny; Douglas, Michael, 1944-; Turner, Kathleen, 1954-; Adler, Warren (Twentieth Century Fox, 2011)
In this blackest of comedies, a perfect 18-year marriage suddenly becomes unglued and the gleefully evil Barbara and Oliver Rose (Kathleen Turner and Michael Douglas) single-mindedly inflict as much misery as possible on each other. Rather than just get divorced, they declare war, fighting to the bitter end over their huge mansion and every possession in it. Not even the calculating guidance of Oliver's lawyer (Danny DeVito) can stop this uncompromising twosome as their vicious battle sends them on an increasingly dark and dangerous path.